Effects of Training on Running Cost and Aerobic Capacity in Individuals with Obesity - Castro, Eliane Aparecida; Silva, Elisangela; Benito, Pedro J; Neiva, Cassiano Merussi; Pessôa Filho, Dalton Müller (International Journal of Sports Medicine, 2023)
This study investigated running cost (CRun), peak oxygen consumption (V̇ O2peak), and ventilatory threshold (VT1) responses to exercise programs for individuals with obesity. Ninety-four individuals (38.2±7.7 years; 33.4±2.9 kg/m²) were assigned into strength (n=24), endurance (n=26), combined (n=22), and physical activity (control, n=22) groups for 22 weeks, plus diet recommendation. The V̇ O2peak, VT1, and CRun were assessed through a maximal incremental step test. The change of V̇ O2peak in combined (9.9%) differed from the other groups, with lower values in women than men (0.7% vs. 6.2%). The VT1 change in combined (16.4%) differed from the strength (4.9%) and physical activity (1.2%) groups, with the change in endurance (12.7%) also being higher than the physical activity group. Only men in the combined group increased absolute V̇ O2peak, while both sexes increased VT1 in the endurance and combined groups. No effects for groups and sex were significant for CRun in moderate (<VT1) or high-intensity (>VT1) running zones, despite CRun changes in <VT1 and >VT1 zones correlated with the alterations of V̇ O2peak and VT1 (r²=0.29–0.59). Therefore, moderate aerobic exercise stimulus is suitable for VT1 improvement in individuals with obesity, with the increase in CRun associated to the chances of increasing V̇ O2peak in men and when combining strength with aerobic exercises.
Keywords: aerobic training; strength training; cardiorespiratory fitness; exercise economy; sex